A combined first principles computational and solid-state NMR study of a molecular crystal: flurbiprofen. - Yates, JR; Dobbins, SE; Pickard, C; Mauri, F; Ghi, P; Harris, R (2005)
The 1H, 13C and 19F magic-angle spinning NMR spectra have been recorded for Form 1 of flurbiprofen. In the case of 19F, spinning sideband analysis has produced data for the components of the shielding tensor. The chemical shift of the hydrogen-bonded proton was found to be 14.0 ppm. Shielding parameters for all three nuclei have been calculated using Density Functional Theory (DFT) together with the Gauge Including Projector Augmented Wave (GIPAW) method which takes full allowance for the repetition inherent in crystalline structures. Such computations were made for the reported geometry, for a structure with all the atomic positions relaxed using DFT, and with only the hydrogen positions relaxed. The relationships of the computed shifts to those observed are discussed. In general, the correlations are good.